Look again : recognize your worth, renew your hope, run with confidence. - Tebow, Tim, 1987-; Gregory, A. J., 1976- (Nelson Books, an imprint of Thomas Nelson, 2025)
"Highlighting his work with some of the world's most vulnerable populations, Tebow unlocks a powerful truth: Everything changes when we learn to see the image of God in every human; ourselves, our neighbors, and even our enemies. With powerful personal stories and profound spiritual principles, Tebow gives readers the tools and inspiration they need to impact their homes, neighborhoods, communities, and culture for good. In Look Again, Tebow inspires you to: stand up to the lies and fight for the truth, see everything and everyone differently, including yourself, and joyfully rediscover the infinite worth of every person in the world, including people society rejects. 'God has done something incredible for you...Not because everything in your life is perfect, but because you know the One who holds your future. And when you know how deeply you're loved, you can step forward boldly, even when the odds are stacked against you.'"--